The Effect of Teacher Competence and Emotional Intelligence on Students Development Character at Senior High School Kristen Barana’ - Anie Threesje Yolanda; Lisa Gracia Kailola; ied Veda R. Sitepu (CV. Creative Tugu Pena, 2021)
This article was to analyze the effect of teacher competence on students’ development character at SMA Kristen Barana, to analyze the effect of teachers’ emotional intelligence on the students’ development character at SMA Kristen Barana and to analyze the effect of teacher competence and teachers 'emotional intelligence simultaneously on students’ development character at SMA Kristen Barana. The researchers used quantitative method in the form of multiple regression. The data were obtained through a research instrument in the form of a questionnaire. Based on the results of teacher's competence testing on student character development, it was known that there was a significant effect of teacher's competence on students’ development character as indicated by the results of the t test where tcount = 5.857 was greater than ttable = 2.040. Based on the results of testing the teacher's emotional intelligence on students development character, it was known that there was a significant effect of emotional intelligence on students development character as indicated by the results of the t test where tcount= 3.920 was greater than ttable = 2.040. The results of multiple regression analysis show that there was an effect of teacher's competence and teacher's emotional intelligence on students’ development character at SMA Kristen Barana. It can be seen from the results of data analysis where Fcount > Ftable, Fcount is 17.860 and Ftable was 3.30. The coefficient of determination was 0.535, meaning that 53.5% of the teachers’ competence and teachers emotional intelligence variables together have an effect on the student development character variables. Keywords: Teachers Competence, Teachers Emotional Intelligence, Development Education Character